When children play, they feel better: organized activity participation and health in adolescents. (December 2015) - Badura, Petr; Geckova, Andrea; Sigmundova, Dagmar; van Dijk, Jitse; Reijneveld, Sijmen
Abstract Background Participation in organized leisure-time activities (OLTA) has been linked to healthy youth development. This study aimed to assess whether participation in OLTA is associated with both physical and mental health in adolescents, and whether this association differs by pattern of activity participation, age and gender. Methods The present study was based on data from the 2013/2014 Health Behaviour in School-aged Children study in the Czech Republic. This data concerned 10, 503 adolescents (49.2 % boys) aged 11, 13 and 15. A cluster analysis was carried out to obtain patterns of activity participation and yielded five groups (all-rounders, artists, individual sports, team sports and inactive). The association between participation in types of OLTA and physical and mental health was analysed using logistic regression models adjusted for age and gender. We also assessed interactions between types of OLTA and gender and age. Results Participation in OLTA was associated with better self-rated health and higher life satisfaction regardless of gender or age. Participation in team or individual sports was associated with better general health and less frequent health complaints in boys, while participation in art activities was associated with lower occurrence of health complaints in girls and 11-year-olds. Conclusion Participation in OLTA is associated with better physical and mental health in adolescents. The association varies by pattern of activity participation and is partly gender- and age-specific.